Difference In Effectiveness Of Fixed Combination Of Cinnarizine 20 Mg And Dimenhydrinate 40 Mg With Betahistine Dihydrochloride 16 Mg In Patients With Meniere's Disease - Nurul Wahidah Yasid; Mochammad Erwin Rachman; Ade Rahmy Sujuthi (Jurnal EduHealth, 2024)
Meniere's disease (MD) is a disorder of the inner ear characterized by hearing loss , tinnitus , and vertigo . In most cases , the disease is slowly progressive and has a significant impact on the social functioning of the affected individual. Hearing loss , tinnitus , and vertigo is common symptomatic complaints with many potential causes , but Meniere's disease is actually quite rare and is essentially a diagnosis of exclusion . This research uses a literature review method by tracing the results of scientific publications in the time period between 2012 and 2024 using 3 databases , namely : Google Scholar , PubMed , and ScienceDirect . A search strategy based on PICO suggests that the fixed combination of cinnarizine and dimenhydrinate is a safe and possibly better treatment options for patients . a combination of cinnarizine and low dose dimenhydrinate is a good choice for treatment . Dimenhydrinate has been proven to be effective in reducing the DHI score and sub- score of GVP sufferers , meaning that combination drugs administration is considered more effective for treating Meniere's disease when compared to monotherapy .